Sex After Sixty - Cohen, May (1984)
Although sexuality is an intrinsic part of one's humanity throughout the lifespan, health professionals frequently ignore the sexual needs and concerns of the elderly. Deterrents to sexual activity may include society's disapproval of sexual expression by the elderly, lack of a partner, the elderly person's own lack of sexual knowledge or belief that nonreproductive sexuality is wrong, and lack of privacy. Physicians must accept elderly people's sexuality and develop attitudes and skills which facilitate communication. It is particularly important to make elderly patients aware that they do not have to have intercourse in order to express their sexuality, and to educate them about the physiological and pathological changes with aging, so they realize these changes need not mean the end of sexual expression.